HUBUNGAN ANTARA DUKUNGAN ORANGTUA, DUKUNGAN SOSIAL TEMAN, DAN HARGA DIRI DENGAN PRESTASI AKADEMIK SISWA KMS PADA JENJANG SEKOLAH MENENGAH PERTAMA DI KOTA YOGYAKARTA - , KHOIRIYA ULFAH, Dr. Fathul Himam, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was aimed to know whether there was any correlation among parentsâ support, friendsâ social support, and self esteem with academic achievement of KMS students. This research is a quantitative research by using regression analysis. The subjects of this research were 103 students of 7th grade and 8th grade in Junior High School. Data used was pure semester score of the students, the result of assessment score that was done by using parentsâ support questioner, friends social support questioner, and self esteem questioner. The result of the analysis showed coefficient of multiple correlation R = 0.230. This value showed that there was no positive correlation among parentsâ support, friendsâ social support, and self esteem with academic achievement of KMS students. By showing F-regression value = 1.839 with significance level 0.145 (p> 0.05). the correlation among variables showed that from third of the independent variables, there was only one variable which had influential correlation with academic achievement